Utilizing Sports Celebrities in Media and Its Impact on Role Modeling Among Adolescents- A Survey Study on a Sample of Algerian Teenagers- - elkhamssa, ramdane (sports creativity, 2024)
This study aims to explore the use of sports celebrities in the media and its impact on role modeling among adolescents, from the perspective of the social learning theory. This is achieved through a theoretical literature review and an attempt to approach it in the context of a survey study on a sample of Algerian teenagers. The study utilizes a descriptive survey methodology, aiming to document and describe phenomena and events as they exist in the current time. An electronic questionnaire was employed to reach the target research population, characterized by its extensive geographical coverage and significant size, estimated at 78 teenagers. The study concludes that the media plays a significant role in enhancing the attractiveness of celebrities by presenting them in the best possible light, focusing on specific aesthetic traits across various programs as role models for adolescents. These celebrities serve as ideal models for adolescents to observe various behaviors, habits, and values, aspiring to emulate and adopt them.